Structural analysis of Al–Ce compound phase in AZ-Ce cast magnesium alloy - Su Juan; Guo Feng; Cai Huisheng; Liu Liang (Journal of Materials Research and Technology, 2019)
The AlvCe intermetallic compound is an important component of the as-cast AZ-Ce magnesium alloy. Accurately determining the type of the Al–Ce compound is a necessary prerequisite for analyzing the alloying mechanism of Ce in the AZ magnesium alloy. In this study, the compound in the as-cast AZ-Ce magnesium alloy was extracted and enriched by electrochemical phase separation. The Al–Ce intermetallic compound was calibrated by X-ray diffraction and transmission electron diffraction. The thermodynamic parameters of the formation of Al4Ce and Al11Ce3 compounds were calculated. The results show that for die casting samples with Ce content of 0.3–1.2 wt%, Al content of 3–9 wt% and diameter of Φ6–Φ24 mm, the Al–Ce compound in the as-cast microstructure is always Al4Ce, instead of other Al–Ce compound. The Gibbs free energy change of Al11Ce3 compound formation reaction in alloy melt is negative compared with Al4Ce, that is, Al11Ce3 compound has stronger forming ability than Al4Ce. The reason why Al4Ce is formed may be that the kinetic conditions are more likely to satisfy the nucleation and growth requirements of the Al4Ce compound for Ce, Al element concentration and atomic ratio. Keywords: AZ-Ce magnesium alloy, Al–Ce compound, Electrochemical phase separation, Phase analysis, Thermodynamic calculation